Analisis Pemasaran Jamur Tiram (Pleurotus Ostreatus) Di Desa Bingkat Kecamatan Pegajahan Kabupaten Serdang Bedagai - Plawer Sekar Arimbi Br. Pakpahan; Zulkarnain Lubis; Khairul Saleh (Universitas Medan Area, 2022)
The purpose of this study was to determine the marketing channels and marketing efficiency of oyster mushrooms in Bangkat Village, Pegajahan District, Serdang Bedagai Regency. The research location in Bangkat Village was chosen purposively. The total population of farmers is 20 farmers. The sampling method used is using the snowball sampling method, so the samples taken in this study were 8 farmers, 2 collectors, 2 merchant traders, 2 chrispy mushroom traders and 10 consumers. The total sample in this study was 24 samples. Methods of data collection using questionnaires, interviews and field observations. Data analysis uses marketing margin analysis. The results of this study indicate that there are 3 marketing channels for oyster mushrooms, namely the first channel selling oyster mushrooms to collectors and collectors selling back to mushroom retailers and traders selling to consumers. In the second channel, farmers sell oyster mushrooms to retailers and then traders sell them to consumers. In the third channel, farmers directly sell mushrooms to consumers. The three marketing channels for oyster mushrooms in the research area are efficient.